2001
DOI: 10.4269/ajtmh.2001.65.341
|View full text |Cite
|
Sign up to set email alerts
|

Invasive amebiasis: challenges in diagnosis in a non-endemic country (Kuwait).

Abstract: Abstract. Invasive zymodemes of the enteric protozoan Entamoeba histolytica infect the large intestine and cause extra-intestinal lesions such as amebic liver abscess (ALA). The clinical manifestations of ALA are protean, particularly in patients presenting in a non-endemic, desert country such as Kuwait, and diagnosis becomes problematic. In this study, we present cases of ALA to illustrate the clinical and diagnostic challenges. For serodiagnosis of ALA, we compared the sensitivity and specificity of the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 11 publications
3
15
0
Order By: Relevance
“…It may also be useful in the evaluation of intestinal and extraintestinal infections where amebiasis is suspected but organisms cannot be detected in feces (152). A microtiter ELISA to detect antibodies to E. histolytica (LMD Laboratories, Inc., Carlsbad, CA) has been shown to be 97.9% sensitive and 94.8% specific for detection of E. histolytica antibodies in ALA patients (84). Serum IgG antibodies persist for years after E. histolytica infection, whereas the presence of IgM antibodies is shortlived and can be detected during the present or current infection.…”
Section: Antibody Detection Testsmentioning
confidence: 99%
“…It may also be useful in the evaluation of intestinal and extraintestinal infections where amebiasis is suspected but organisms cannot be detected in feces (152). A microtiter ELISA to detect antibodies to E. histolytica (LMD Laboratories, Inc., Carlsbad, CA) has been shown to be 97.9% sensitive and 94.8% specific for detection of E. histolytica antibodies in ALA patients (84). Serum IgG antibodies persist for years after E. histolytica infection, whereas the presence of IgM antibodies is shortlived and can be detected during the present or current infection.…”
Section: Antibody Detection Testsmentioning
confidence: 99%
“…These nine patients may be at an early stage of the infection and therefore had undetectable levels of anti-E. histolytica antibodies. According to previous reports, serology may be negative in patients in the acute phase within 7-10 days postinfection (Hira et al, 2001;Fotedar et al, 2007). At this stage, liver abscess may have developed and thus early detection is crucial to avoid complications.…”
Section: Discussionmentioning
confidence: 92%
“…Most of the other studies also had observed the similar laboratory findings. [23][24][25][26] In the present study pleuropulmonary complications were most common of which right side pleural effusion is most common, some cases of empyema also observed. Second most feared complication in our study is septicemia and shock followed by sub hepatic collection and peritonitis.…”
Section: Discussionmentioning
confidence: 99%